2009
DOI: 10.1093/fampra/cmp007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment satisfaction of diabetic patients: what are the contributing factors?

Abstract: Treatment satisfaction is lower among diabetic patients who have a lower educational level, who are insulin treated or have a diabetic complication and is related to difficulties in taking medications and coming to follow-up visits. Addressing the specific needs of these patients might be effective in improving their satisfaction, thus having a positive influence on other clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
128
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(155 citation statements)
references
References 14 publications
20
128
2
5
Order By: Relevance
“…Satisfaction and efficacy of switching from daily dipeptidyl peptidase-4 inhibitors to weekly trelagliptin in patients with type 2 diabetes -Randomized controlled studyMayuko Oita 1) , Hideaki Miyoshi 1) , Kota Ono 2) , Akinobu Nakamura 1) , Kyu Yong Cho 1), 2) , Hiroshi Nomoto 1) , Kohei Yamamoto 1) , Kazuno Omori 1) , Naoki Manda 3) , Yoshio Kurihara 4) , Shin Aoki 5) and Tatsuya Atsumi 1) intensive metabolic controls, especially adequate glycemic control, are necessary [1]. Therefore, it is important for patients to maintain a favorable lifestyle and continue the necessary treatment with good medication adherence over a long period time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction and efficacy of switching from daily dipeptidyl peptidase-4 inhibitors to weekly trelagliptin in patients with type 2 diabetes -Randomized controlled studyMayuko Oita 1) , Hideaki Miyoshi 1) , Kota Ono 2) , Akinobu Nakamura 1) , Kyu Yong Cho 1), 2) , Hiroshi Nomoto 1) , Kohei Yamamoto 1) , Kazuno Omori 1) , Naoki Manda 3) , Yoshio Kurihara 4) , Shin Aoki 5) and Tatsuya Atsumi 1) intensive metabolic controls, especially adequate glycemic control, are necessary [1]. Therefore, it is important for patients to maintain a favorable lifestyle and continue the necessary treatment with good medication adherence over a long period time.…”
mentioning
confidence: 99%
“…Therefore, it is important for patients to maintain a favorable lifestyle and continue the necessary treatment with good medication adherence over a long period time. Patients who are dissatisfied with their treatment are less likely to adhere to that treatment [2,3], and non-adherence to treatments for type 2 diabetes can result in poor glycemic control [4][5][6][7], which increases the risk of complications leading to disease deterioration.…”
mentioning
confidence: 99%
“…51 A survey conducted among 630 diabetes patients also found that treatment satisfaction was lower in those taking insulin. 52 According to this survey, other factors independently associated with lower treatment satisfaction were female gender, diabetes complications and poor adherence. 52 The findings of this study cannot be generalized because of several limitations, including the observational, open-label design, the small sample size and the absence of a specific clinical evaluation of frailty.…”
Section: Discussionmentioning
confidence: 80%
“…52 According to this survey, other factors independently associated with lower treatment satisfaction were female gender, diabetes complications and poor adherence. 52 The findings of this study cannot be generalized because of several limitations, including the observational, open-label design, the small sample size and the absence of a specific clinical evaluation of frailty. However, the present study describes a group of difficult-to-treat, real-world patients who closely resemble those typically encountered in daily clinical practice.…”
Section: Discussionmentioning
confidence: 80%
“…MedPodml 2018, 69(1): [15][16][17][18][19][20][21][22] telesnom masom, ukazujući da zadovoljstvo terapijom i te kako utiče na sam ishod lečenja (9,10). Zbog svoje prirode, toka, neophodnih životnih promena, dijabetes umnogome utiče na kvalitet života.…”
Section: Uvodunclassified